An Algorithm for Quantitatively Calculating I/Q Gain and Phase Mismatch - Gang Yang; Jin Liu (Institute of Advanced Engineering and Science, 2012)
The in-phase and quadrature modulator (IQ modulator) is a key component in modern wireless transmitter. It provides a convenient method for modulating data bits or symbols onto an RF carrier. It has become the architecture of choice for implementing transmitter signal chains for end applications such as cellular, WiMAX, and wireless point-to-point. However, there are several non-ideal aspects of analog IQ modulator, include IQ gain imbalance, imperfect quadrature, and LO leakage. These imperfections will result in image spectral and degrade MER of the modulator, which in turn degrades bit error rate (BER). Gain matching and phase compensation both affect the total amount of image rejection. Factory calibration can detect the IQ gain and phase mismatch in different frequency and store the correction coefficients in nonvolatile memory. The key issue is how to get the exact mismatch. In this paper, a mathematical model of IQ modulator was established and an analytic solution is obtained about how to get the exact mismatch parameters. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.872